Teachers' and learners' perceptions towards translanguaging pedagogy in English First Additional Language among Grade 7 Tshivenda learners in Vhembe District, Limpopo Province, South Africa - Ralushai, Mpfariseni Moses (My University, 2024)
This study reports on a study conducted among bilingual Grade 7 teachers and learners in the Vhembe District, Limpopo Province, South Africa. The purpose of the study was to explore the perceptions of teachers and learners regarding their use of the translanguaging pedagogy in the teaching and learning of English FAL. The study comprised 9 Grade 7 English FAL teachers and 90 Grade 7 learners who registered for English FAL and Tshivenḓa Home Language (HL) at 3 different primary schools situated in the Luvuvhu Circuit, Vhembe District. A multiple case study of three primary schools was conducted using the mixed method to collect data concurrently using the four instruments, that is, classroom observation schedules, closed-ended questionnaires, focus groups, and semi-structured interviews. The overall results of the study revealed that the majority of Grade 7 teachers and learners have a positive outlook on the translanguaging pedagogy in the teaching and learning of English FAL. Alternation and flexible use of Tshivenḓa HL and English is permitted, and HL was used to scaffold and accelerate the learning of English FAL. On the other hand, the study revealed that some of these Grade 7 teachers and learners objected to the use of the translanguaging approach to promote the use of an English-only approach to accelerate the learning of English FAL in their classrooms. As the strict language isolationist belief is still widely accepted and utilised by some Grade 7 teachers and learners, the researcher was prompted to recommend an awareness of the cognitive and affective benefits of the translanguaging pedagogy in the second language (L2) classrooms and the need to value the learners' full linguistic repertoire that they bring to their classrooms for learning purposes.
Thesis (Ph.D. (English Studies)) -- University of Limpopo, 2024
Keywords: Perceptions; Translanguaging approach; Scaffold; Linguistic repertoire; English-only approach; Bilingual; Second language (L2); Home language (HL).; Translanguaging (Linguistics); Language and languages -- Variation; Education, Bilingual -- South Africa; Linguistics; English language -- Study and teaching